Avaliação da qualidade de vida de pacientes enteroparasitados por meio de um instrumento genérico (SF- 36) - Cavalcante, Ulanna Maria Bastos (2015)
The Quality of Life (QOL) has become understood as subjective quality of life or quality of life perceived by the people, influenced mostly by the World Health Organization (WHO) states that health is not restricted to the absence of disease, but encompasses the individual perception of a complete physical, mental and social well-being. Thus, the concept of QOL has been described as something dynamic, multidimensional and how it is perceived is different for everyone. Thus, the intestinal parasitism influence on QoL, as it constitutes a serious public health problem and contributes to economic, social, and health, especially in developing countries, one of the main factors debilitating the population. The objective of this study was to evaluate the quality of life of patients with intestinal parasites treated at a Joao Pessoa Public Service. This is an observational cross-sectional study and descriptive analysis, conducted with a sample of 135 patients treated at the Clinical Laboratory of the University Hospital Lauro Wanderley, in the city of João Pessoa - PB. The statistical method of logistic regression was used to explain what categorical variables become relevant for intestinal parasites and to support decision making. The sample showed 94 (69.6%) women and 41 (30.4%) men, 73 (54%) brown / brown over the age of 54 50 (37%). The most common species of parasite was Ascaris lumbricoides (28.75%), followed by Giardia lamblia (25.0%), Endolimax nana (18.75%) and Entamoeba coli (12.5%). The analysis of variables related to the SF-36 instrument, which assesses QoL, it was observed that the domains general health and physical aspects had lower averages, being the most affected in the opinion of patients, with an average of 46.77 and 48 , 76, respectively. In the selection of the first model the dependent variable is parasitic and non-parasitized, the variables that showed statistical significance (α = 10%) were type of animal, marital status, constipation, functional capacity domain, domain pain, mental health domain, vomiting and abdominal cramping. In the second model, only positive patients, the response variable was the presence or absence of pathogenic parasite. The significant variables were: decreased work / activities, comorbidity, abdominal colic, moderate activities, physical aspect domain, vomiting, sanitation and animal type. The logistic regression model developed showed that the selected models can be used as a reference for assessing the quality of life of patients and enteroparasitados identify the domains of the SF-36 questionnaire that affect the quality of life of these individuals. It was identified some risk factors for parasitic infections that can be prevented or controlled through planning actions aimed at the prevention and control of intestinal parasites.